2016
DOI: 10.2106/jbjs.15.00898
|View full text |Cite
|
Sign up to set email alerts
|

The Accuracy of Imaging Techniques in the Assessment of Periprosthetic Hip Infection

Abstract: Diagnostic Level IV. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
77
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(87 citation statements)
references
References 62 publications
5
77
0
5
Order By: Relevance
“…FDG-PET is increasingly used and has proposed potential in the diagnosis of PJI, especially regarding hip arthroplasty [10, 39, 51, 58]. Although this technique offers advantages such as time efficiency, increased resolution, and the use of low-dose CT, our results revealed that this technique was less specific in diagnosing periprosthetic knee infection than combined leukocyte and bone marrow scintigraphy and antigranulocyte scintigraphy (Fig.…”
Section: Discussionmentioning
(Expert classified)
See 1 more Smart Citation
“…FDG-PET is increasingly used and has proposed potential in the diagnosis of PJI, especially regarding hip arthroplasty [10, 39, 51, 58]. Although this technique offers advantages such as time efficiency, increased resolution, and the use of low-dose CT, our results revealed that this technique was less specific in diagnosing periprosthetic knee infection than combined leukocyte and bone marrow scintigraphy and antigranulocyte scintigraphy (Fig.…”
Section: Discussionmentioning
(Expert classified)
“…Leukocyte scintigraphy is assumed to be a more specific-imaging modality and has a long history of use in detection of infections [11, 51]. However, our meta-analysis showed that this technique alone may not be the preferred modality for confirming periprosthetic knee infection, given that it has only moderate specificity (77%) (Table 6).…”
Section: Discussionmentioning
confidence: 95%
“…Bone scintigraphy with technetium Tc 99m ( 99m Tc)labeled diphosphonates or, alternatively, sodium fluoride F 18 PET 20 can be used to assess osteoblastic activity around the prosthesis. Because sensitivity is high, 21,22 normal findings can be considered strong evidence against the presence of PJI. 23 Specificity, however, generally is low 21,22 ; positive findings can indicate either PJI or aseptic loosening.…”
Section: Role Of Imaging Including Fludeoxyglucose F 18 Positron Emimentioning
confidence: 99%
“…Because sensitivity is high, 21,22 normal findings can be considered strong evidence against the presence of PJI. 23 Specificity, however, generally is low 21,22 ; positive findings can indicate either PJI or aseptic loosening. Moreover, a bone scan may be positive for at least 2 years after hip replacement and at least 5 years after knee replacement due to physiologic bone remodeling.…”
Section: Role Of Imaging Including Fludeoxyglucose F 18 Positron Emimentioning
confidence: 99%
See 1 more Smart Citation